Math, asked by chauhanshekhar61, 6 months ago

find the radius and centre of the circule x^2+y^-6x+8y+9=0​

Answers

Answered by amansharma264
8

EXPLANATION.

Equation of circle → x² + y² - 6x + 8y + 9 = 0.

General equation of circle

→ x² + y² + 2gx + 2fy + c = 0.

Centre of the circle = ( -g, -f).

Radius of the circle = √g² + f² - c = 0.

Compare both the equation we get,

→ Centre = ( 3 , -4).

→ radius = √ (3)² + (-4)² - 9 = 0.

→ radius = √ 9 + 16 - 9 = 0.

→ radius = √ 16 = 4.

More information.

 \sf \: case \:  = 1 \\  \\  \sf \: \implies \:   c_{1} c_{2}  >  r_{1} \:  +  \: r_{2} \:  \\  \\ \sf \: \implies the \: distance \: between \: centre \: is \: greater \: than \: the \: sum \: of \: radii

\sf \: \implies  \: case \:  = 2 \:  \implies \:  c_{1} c_{2} \:  =  r_{1} \:  +  \: r_{2} \\  \\ \sf \: \implies the \: distance \: between \: the \: centre \: is \: equal \: to \: the \: sum \: of \: radii

\sf \: \implies case \:  = 3 \implies c_{1} c_{2} <  r_{1} \:  +  \:  r_{2} \\  \\ \sf \: \implies  \: the \: distance \: between \: the \: centre \: is \: less \: than \: sum \: of \: radii

\sf \: \implies  \: case \:   = 4 \implies \:  c_{1}c_{2} \:  =  | r_{1} \:   -  \:  r_{2} |  \\  \\ \sf \: \implies  \: the \: distance \: between \: centre \: is \: equal \: to \: the \: difference \: of \: radii

\sf \: \implies  \: case \:  = 5 \implies \:  c_{1} c_{2} <  | r_{1} \:  -  \:  r_{2} |  \\  \\ \sf \: \implies the \: difference \: between \: the \: centre \: is \: less \: than \: the \: difference \: of \: radii

Answered by Anonymous
0

Correct question= How do you find the center and radius of the circle x2+y2−6x+8y=0?

Solution⬇️

The equation of a circle with radius r and center (h, k) in standard form is (x - h)^2 + (y - k)^2 = r^2.

The equation given is x^2 + y^2 - 6x + 8y + 9 = 0

x^2 + y^2 - 6x + 8y + 9 = 0

=> x^2 - 6x + y^2 + 8y + 9 = 0

=> x^2 - 6x + 9 + y^2 + 8y + 16 = 9 + 16 - 9

=> (x - 3)^2 + (y + 4)^2 = 4^2

This is the equation of a circle with center (3, -4) and radius 4

The standard form of x^2 + y^2 - 6x + 8y + 9 = 0 is (x - 3)^2 + (y + 4)^2 = 4^2

Similar questions